Sex differences of proximal tibia anthropometry in a Chinese population: comparison with sizing of tibial implants - Bo Yang; Ming Chen; Xiang-hui Huang; Shizhang Liu; Yanhai Chang; Peng-zhen Lei (Journal of Orthopaedic Surgery and Research)
Abstract Background Matching tibial component with resected tibia dimensions is essential for good clinical outcomes in total knee arthroplasty.The aim of this study was to determine the sex differences in anthropometry at the surface of the resected proximal tibia in Chinese population and compare the anthropometric values with the dimensions of available tibial components currently used in China. Methods The anthropometric characteristics of the proximal tibias in 241 Chinese individuals (121 males, 120 females) were assessed via computed tomography imaging. We measured the mediolateral (ML), anteroposterior (AP), medial and lateral anteroposterior dimensions and the ML/AP aspect ratio of the resected proximal tibial surface. The ML/AP aspect ratios were classified into 3 groups on the basis of the AP dimensions (< 48 mm, 48–51 mm, > 51 mm) to compare sex differences. All the anthropometric data were compared with the dimensions of the six tibial components currently used. Results The tibias ML and AP dimensions of females were significantly smaller than that of males (69.5 ± 3.4 mm, 46.7 ± 2.3 mm vs. 78.4 ± 3.2 mm, 52.6 ± 2.9 mm ). We found females had a smaller ML/AP aspect ratio than males in the subgroups (< 48 mm P = 0.009; 48–51 mm P < 0.001; >51 mm P = 0.043). Compared with component sizes, there was a mismatch between tibial morphology and the dimensions of all the implants. Tibial components with smaller AP measurements were undersized in the ML dimension, and those with larger AP measurements were oversized in the ML dimension in males and females. Conclusion In the Chinese population, females have smaller dimensions and ML/AP aspect ratios than their male counterparts. The results of this study can provide fundamental data on designing optimal tibial components, especially for design of sex-specific prostheses with different ML/AP aspect ratios for the Chinese males and females.